Legal Pluralism and the Social Anomaly of Halal Governance: MSME Compliance and Market Negotiation in Lombok's Halal Tourism Regulation - Wathoni, Abdul Wahid; Hidayah, Nur; Suhaimi, Ahmad; Adnan, Muh; Pitaloka, Lolla; Kilwakit, Marifat (Fakultas Syariah UINSI Samarinda, 2025)
Halal product assurance in Indonesia remains constrained by the gap between formal regulatory frameworks and the existing conditions and realities of Micro, Small, and Medium Enterprises (MSMEs). This study investigates how hybrid governance settings, where state law, local socio-cultural norms, and market incentives coexist and shape MSME compliance with halal certification requirements. Focusing on the tourism-dependent economy of Gili Trawangan, the article employs a qualitative socio-legal methodology, combining in-depth interviews, field observations, and document analysis. Guided by Critical Legal Pluralism, Maqāṣid al-Syarī‘ah, and Substantialist–Formalist Compliance Theory, the findings identify three distinct compliance pathways: adoption, adaptation, and resistance. These patterns emerge from actors' strategic negotiations across multiple normative orders, mediated by their compliance orientations and prioritization of hifẓ al-māl, hifẓ al-dīn, and hifẓ al-nafs. The study argues that effective halal governance cannot rely solely on legal enforcement but must realign economic and religious–ethical objectives to make those conditions mutually reinforcing. This reconceptualisation contributes to academic debates on legal pluralism in Islamic economic governance, offering policy recommendations to harmonise formal law with socio-economic contexts in tourism-based Muslim-minority regions.